2011
DOI: 10.4049/jimmunol.1100058
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TLR2 Enhances Tight Junction Barrier in Epidermal Keratinocytes

Abstract: The epidermis has developed physical and immunological barriers that prevent infiltration of deleterious chemicals and pathogens. As a first step to understanding the relationship between these barriers, we investigated whether TLR2 activation functionally alters tight junctions (TJs) in cultured human keratinocytes. Stimulation with peptidoglycan, a ligand for TLR2, elevated the TJ-associated barrier in the space of 3 h. The increase in TJ-associated barrier function due to peptidoglycan stimulation was suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
95
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 36 publications
11
95
0
4
Order By: Relevance
“…In agreement with a single previous study (23), peptidoglycan also induced increased TEER in keratinocytes. However, the changes observed were strikingly different from those seen with whole lysates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with a single previous study (23), peptidoglycan also induced increased TEER in keratinocytes. However, the changes observed were strikingly different from those seen with whole lysates.…”
Section: Discussionsupporting
confidence: 93%
“…Rather, they demonstrated activation of protein kinase C alpha (PKC␣), an enzyme involved in TJ assembly (22). However, their study used ligands rather than whole organism lysates, and they also measured TEER over shorter times than in the present study (23). We also show that use of ligands such as peptidoglycan increases TEER.…”
Section: Discussionmentioning
confidence: 48%
“…For example, stimulation of primary human keratinocytes with TLR2 ligands enhances the barrier function of TJs. 54,55 An increase in cldn-1, cldn-23, occludin, and ZO-1 expression was observed commensurate with changes in barrier function 55 while, Yuki et al 54 demonstrated occludin-phosphorylation by atypical protein kinase C (aPKC). Similarly, treatment of human epidermis wounded by repeated tape stripping (e.g., model of mechanical injury) with TLR2 agonists enhanced skin barrier recovery (as measured by transepidermal water loss [TEWL]).…”
Section: Tj and Innate Immune Barriermentioning
confidence: 99%
“…(26) In addition, it is also reported that activation of toll like receptor (TLR)-2 plays a role on tight junction barrier via the protein kinase in the tight junction biogenesis. (27) Moreover, IL-4 and IL-13 also promote keratinocyte CLDN-1 expression. (27) Thus TLR-2 activation enhanced expression of CLDN-1 in keratinocytes of AD patients.…”
Section: Factors Influence On Skin Barrier Dysfunctionsmentioning
confidence: 99%
“…(27) Moreover, IL-4 and IL-13 also promote keratinocyte CLDN-1 expression. (27) Thus TLR-2 activation enhanced expression of CLDN-1 in keratinocytes of AD patients. In addition, TLR-2 lacking mice showed delayed or incomplete barrier recovery.…”
Section: Factors Influence On Skin Barrier Dysfunctionsmentioning
confidence: 99%